The Independence of Maximal Intimal Thickening from Severity of Balloon Injury in the Rabbit Aorta - Waissbluth, Alvaro D.; Schwartz, David; Abendschein, Dana R.; Eisenberg, Paul R. (Thrombosis and Haemostasis, 1999)
Endothelial injury induces intimal thickening, but whether more extensive injury increases the extent of neointimal proliferation in the rabbit aorta is not well defined. We induced graded injury in the abdominal aortas of rabbits and maximal intimal/medial (I/M) area and thickness ratios were calculated from aortic cross sections harvested 2 weeks after injury. The degree of injury was verified by blinded observers who graded the extent of disruption of the internal elastic laminae. Intimal thickening was not significantly different after severe injury (mean maximal I/M area ratio 0.32 ± 0.02 [SE], n = 16) compared with moderate injury (0.23 ± 0.02, n = 8, p = 0.24), but was greater than that induced by mild injury (0.08 ± 0.01, n = 7, p <0.0001). The ratio of the maximal I/M thickness was similar in all groups (I/M thickness ratio 0.68 ± 0.04, 0.73 ± 0.04, and 0.56 ± 0.04 for severe, moderate, and mild focal injury groups, respectively; p = 0.19). Thus, balloon injury of the rabbit aorta induces reproducible thickening of the intima by 2 weeks. The maximal I/M area ratio is dependent on the extent of injury, while the maximal intimal thickening is independent.